Modernization of Existing Level Crossings in the Areas of Construction of the European Standard Railway Track in Ukraine - Kurhan, M. B.; Kurhan, A. M.; Luzhytskyi, O. F.; Ivanov, R. V.; Khmelevska, N. P. (Science and Transport Progress, 2024)
Purpose. The article aims to analyze modern technological solutions to improve the level of safety at railway crossings, prevent emergencies and ensure uninterrupted traffic. Methodology. The study is based on the use of mathematical modeling and numerical methods to analyze the impact of modernization and new projects on the level of safety at railway crossings. Using computer modeling, mathematical models were built that reflect different scenarios of crossings. Based on the data obtained, the effectiveness of the proposed measures was assessed and recommendations for further optimization of the security system were developed. To evaluate the effectiveness of the proposed measures, a system of indicators has been developed to quantify the level of safety of railway crossings before and after modernization. These indicators take into account the daily intensity of train traffic through the crossing, the daily intensity of traffic on the road, the equipment of the crossing, the radius of the curve in the plan and the longitudinal slope of the road on the approaches to the crossing. Findings. An improvement of the method of the final accident rate, which is one of the most common tools for assessing traffic safety at railroad crossings, is proposed. The application of this method made it possible to quantify the level of risk of accidents and analyze the effectiveness of measures aimed at improving safety. The method is relatively easy to use and does not require complex mathematical calculations, and allows taking into account a wide range of factors affecting traffic safety at a level crossing, such as traffic volume, design features of the level crossing, availability of signaling, etc. The final coefficient was used to compare the safety level of different crossings and track the dynamics of changes in their equipment over time. This made it possible to identify crossings that require priority modernization, as well as to predict changes in the initial and calculated data and plan measures to introduce innovative technologies that improve traffic safety at crossings. Originality. An integrated model for assessing the safety of railroad crossings has been developed that takes into account not only traditional indicators (frequency of accidents, traffic intensity) but also new factors such as equipment reliability, human factor, and the impact of external conditions. The proposed model makes it possible to determine a more accurate risk forecast and choose optimal solutions for the modernization of level crossings, taking into account specific operating conditions. Practical value. The formulated recommendations can be used to develop effective programs for the modernization of railway crossings in Ukraine. The implementation of the proposed technologies will increase the level of traffic safety by 20% and reduce the average waiting time at a crossing by 15%. In addition, it will help to increase railroad capacity and reduce infrastructure maintenance costs.